2019
DOI: 10.1103/physreva.99.022506
|View full text |Cite
|
Sign up to set email alerts
|

Building principle of triatomic trilobite Rydberg molecules

Abstract: We investigate triatomic molecules that consist of two ground state atoms and a highly excited Rydberg atom, bound at large internuclear distances of thousands ofÅngstroms. In the molecular state the Rydberg electron is in a superposition of high angular momentum states whose probability densities resemble the form of trilobite fossils. The associated potential energy landscape has an oscillatory shape and supports a rich variety of stable geometries with different bond angles and bond lengths. Based on an ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 48 publications
0
26
0
1
Order By: Relevance
“…A central finding from research on polyatomic ULRMs is that binding energies of s-state ULRMs are to a good approximation additive [13], i.e. integer multiples of the number of ground-state atoms, whereas binding energies of polyatomic ULRMs with angular momenta l > 0 are non-additive and involve threeand higher body forces [15,17,18,50]. Since the only experimentally confirmed polyatomic ULRMs with l > 0 are d-state trimers, it is an interesting challenge for future experiments to detect novel polyatomics with more atoms, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A central finding from research on polyatomic ULRMs is that binding energies of s-state ULRMs are to a good approximation additive [13], i.e. integer multiples of the number of ground-state atoms, whereas binding energies of polyatomic ULRMs with angular momenta l > 0 are non-additive and involve threeand higher body forces [15,17,18,50]. Since the only experimentally confirmed polyatomic ULRMs with l > 0 are d-state trimers, it is an interesting challenge for future experiments to detect novel polyatomics with more atoms, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the order of these spacings differs from triatomic low-l Rydberg molecules, where the energy spacing of bending motion is typically much smaller than stretching motion [20]. It also differs from the trilobite trimer, as shown by an example in reference [23] where the spacing of bending and stretching modes is almost equal.…”
Section: Nuclear Wave Functions and Vibrational Spectramentioning
confidence: 95%
“…The studies of trilobite trimers in Refs. [16,23] found that the eigenvalues of Eq. 4 are essentially identical to those computed using the full Rydberg basis, consisting of states with finite quantum defects and multiple Rydberg manifolds.…”
Section: Computational Approach To the Electronic Structure And Born-mentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of ultracold Rydberg excitations in Bose-Einstein condensates, a subfield devoted to the study of long-range Rydberg molecules, known colloquially as trilobite molecules, has developed [7][8][9]. Experiments have resolved the vibrational spectra of Rydberg dimers, trimers, and so forth, and have sparked significant theoretical interest from the perspective of many-body physics [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. At the same time, attention has shifted towards experiments which use the Rydberg atom to probe the surrounding condensate and establish a "microscopic laboratory" to study electron-atom and ion-atom scattering [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%